خطاب عن طوفان الأقصى في خبر الجزيرة نت: دراسة سيميائيّة اجتماعيّة - An Shori, Alam; Al Anshory, Abdul Muntaqim (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah, 2023)
The study about "Discourse of Thufanul Aqsha on Al Jazeera Net News: A Social Semiotic Study" is interesting for in-depth study. It was said that because the news of the Thufanul Aqsha was news that attracted the attention of all parties. The purpose of this writing is to understand two situations: 1.) To know the social context in Al Jazeera Net news about Thufanul Aqsha; 2.) How the Palestinian struggle exists. The method that's used is to study the references using a qualitative approach based on social semiotics, detail the data by reading news and articles, analyze it using the method of Huberman and Miles. We found two results in this research: 1.) The social context was found in Al Jazeera Net news about Thufanul Aqsha. 2.) Thufanul Aqsha as the presence of the struggle for Palestinian independence. The result of research is that the Thufanul Aqsha as the existence of struggle for Palestinian independence. دراسة الّتي تحت العنوان "خطاب طوفان الأقصى في خبر الجزيرة نت: دراسة سيميائيّة اجتماعيّة" هي أمر مثير للدّراسة المتعمّقة. قيل هكذا لأنّ صار خبر طوفان الأقصى خبرا اهتماما لجميع الأطرف . وقصد من هذه الكتابة هو لتفهيم حالين: الأوّل، لمعرفة السّياق الاجتماعيّ في أخبار الجزيرة نت حول طوفان الأقصى، الثّاني، كيف وجود النّضال فلسطينيّين. وأمّا الطّريقة الّتي تستخدم هي دراسة المراجع بالمنهج النّوعيّ على أساس سيميائيّة اجتماعيّة، والتّفصيل البيانات بقراءة الأخبار والمقالت ثمّ يحلّ بطريقة هبرمن وملس . وجدنا حاصلان في هذا البحث: الأوّل،  وجد السّياق الاجتماعيّ في خبر الجزيرة نت حول طوفان الأقصى. الثاني، طوفان الأقصى كوجود النّضال من أجل الاستقلال الفلسطيني. والنّتيجة في هذا البحث أنّ طوفان الأقصى كوجود النّضال من أجل الاستقلال فلسطيني.